The Economic Multiplier Effect of EU Cohesion Policy: Evidence from Portugal's Alentejo Region (2014-2020) (European Journal of Marketing and Economics, 2025)
This study provides a comprehensive assessment of the economic multiplier effects generated by European Structural and Investment Funds (ESIF) in Portugal's Alentejo region during the 2014-2020 programming period. Through a novel application of regional input-output analysis, we quantify how €1.28 billion in ESIF allocations stimulated complementary investments across seven strategic domains: (1) infrastructure modernization (32% of total), (2) cultural/natural heritage (18%), (3) energy efficiency (15%), (4) ICT deployment (12%), (5) R&D initiatives (11%), (6) urban rehabilitation (7%), and (7) mobility improvements (5%). Our findings demonstrate robust multiplier effects ranging from 1.25-1.50x, with sectoral variations revealing highest returns in ICT (1.72x) and R&D (1.68x) versus more modest infrastructure impacts (1.19x). The analysis identifies three key transmission channels: (i) crowding-in of private capital (accounting for 38% of induced investment), (ii) intermunicipal cooperation effects (27%), and (iii) supply-chain linkages (35%). Spatial econometric techniques further reveal that funds targeting urban centers generated 22% greater spillovers than rural allocations. These results provide empirical support for cohesion policy's effectiveness in peripheral regions, while suggesting refinements to optimize future fund allocation—particularly through enhanced focus on knowledge-economy investments and improved rural-urban synergies.
Keywords: EU cohesion policy, regional multipliers, input-output analysis, Alentejo region, structural funds effectiveness, territorial development, investment crowding-in, H2020 impacts